Metamagneto em campos magnéticos uniforme e aleatório - Weizenmann, Antonio (2005)
The phase diagram of an Ising metamagnet in an uniform magnetic field and in a random magnetic field is studied using a mean field theory derived from Bogoliubov variational principle. The phase diagram displays tricritical behavior and reentrance phenomenon for determined values of the random magnetic field above a certain critical value. The reentrance phenomenon is due to the competition between the other interactions ferromagnetic, anti-ferromagnetic, uniform magnetic field and the random magnetic field. In particular, if the model exhibits a first-order transition in zero random field, then a bimodal distribution never destroys this first-order transition, in contradiction to the case of a trimodal distribution.